Common Challenges and Solutions in Narrative Review Articles - Mahla Salajegheh (مجله علمی دانشگاه علوم پزشکی کردستان, 2023)
One type of review study is a narrative review that is used to summarize the studies of a field. The most common use of this type of review is when there is no single hypothesis on the subject. Therefore, these studies provide an opportunity to present the knowledge and experience of the author in a specific area. Some authors encounter errors in writing narrative review articles that reduce the quality of the article.